Investigating Trends and Future Research SMEs Performance: Perception from Analysis Bibliometrics - Nanang Rusliana; Aso Sukarso; Dwi Hastuti LK; Asep Muhammad Adam; Galih Nugraha (Politeknik Negeri Bali, 2025)
This research explores the scientific activities and general trends of SMEs performance. Bibliometrics analysis was used against 456 articles from 2000 to 2022 to see the general perspective of SMEs performance. The database used to collect data is Scopus with the search keyword